Kinetic and Thermodynamic Study on the Inhibition of Adenosine Deaminase by Theobromine - Saboury, A.A.; Bagheri, S.; Ataie, G.; Moosavi-Movahedi, A.A.; Hakimelahi, G.H.; Cristalli, G.; Mardanian, S. (Asian Journal of Chemistry, 2016)
Kinetic and thermodynamic studies were made on the binding of theobromine on the activity of adenosine deaminase (ADA) in 50 mM sodium phosphate buffer pH 7.5 at 300 K, using UV spectrophotometry and isothermal titration calorimetry (ITC). Theobromine acts as a competitive inhibitor. A graphical fitting method was used for determination of binding constant and enthalpy of inhibitor binding by using ITC data. The dissociation-binding constant is equal to 318 μM by the calorimetry method, which agrees well with the value of 311 μM for the inhibition constant that was obtained from the spectroscopy method. The molar enthalpy and entropy of binding for theobromine are -15.80 kJ mol-1 and 14.30 J K-1 mol-1, respectively. So the binding process for theobromine on ADA is spontaneously by both enthalpy an entropy driven.